Computational tools as an aid to Mathematics learning: GeoGebra (Research, Society and Development, 2023)
Technologies are more advanced every day, and also more present in everyone's daily life. And in schools it is no different, in recent years much research has been done in search of methods that contribute to good learning through it. This work aims at an experience report with the objective of conceptualizing the richness that the use of software brings to the teaching of Mathematics, the investigation was carried out through a case study with a view to sharing experiences of a CI project in the use of technologies in the classroom. It consists of the application of the workshop using GeoGebra software in the teaching of Mathematics in a training group of Computer Technicians. It can be seen how important software is for teaching, especially in Mathematics classes, as students justify that the use of GeoGebra software contributes to better understanding and visualization, in addition to offering some facilities for interpreting Mathematics regarding the content of Functions of the 10th Degree.